Correlation Between Knowledge, Mother's Support, Peer Support with Anxiety to Confront Menarche among Adolescents at Elementary school: A Correlational Study - Nurul Fauziyah; Rizki Fitryasari; Aria Aulia Nastiti (Pediomaternal Nursing Journal, 2020)
Introduction: Menarche can affect the physical and psychological changes of a young woman; one of them is anxiety. The purpose of this research was to know the relationship between knowledge, mother's support, and peer support with adolescent's anxiety in confronting menarche.Methods: This study was an analytic correlational-cross sectional design. The population is a fourth-grade student of Elementary School Rungkut Menanggal 1, Rungkut Menanggal 2, and Rungkut Kidul 1 school year 2018/2019, which has not experienced menarche, totaling 148 students. The respondents were 108 students that had been recruited by the Random Sampling method with slovin formula. The Independent variables are knowledge, maternal support, and peer support. The dependent variable was adolescent's anxiety in confronting menarche. The data were collected using a questionnaire, analyzed using the spearmen rank correlation test.Results: The result of statistical test showed that knowledge (r = -0.626 p = 0.018), mother’s support (r = -0.725 p = 0.000) and peer support (r = -0.581 p = 0.000) correlated with the anxiety of adolescent’s anxiety in confronting menarche.Conclusion: Knowledge, mother's support, and peer support can reduce adolescent's anxiety in confronting menarche because it can be used as a provision to prepare for menstruation.